ORGANIZATIONAL AND HRM STRATEGIES IN KOREA: IMPACT ON FIRM PERFORMANCE IN AN EMERGING ECONOMY. - Bae, J.; Lawler, J. J. (Academy of Management Journal, 2000)
To examine the effects of organizational strategic variables, such as management values regarding human resource management (HRM) and the sources of competitive advantage, we developed a model and tested it with data from 138 firms in Korea. The workers studied were nonmanagers. Firms with high scores on valuing HRM and people as a source of competitive advantage were more likely to have high-involvement HRM strategies. These variables also had positive effects on firm performance. In addition, firms with high-involvement HRM strategies had better performance.